Models of Teaching : Connecting Student Learning with Standards. - Dell'Olio, Dr. Jeanine M. M. (SAGE Publications, 2007)
Models of Teaching: Connecting Student Learning with Standards features classic and contemporary models of teaching appropriate to elementary and secondary settings. Authors Jeanine M. Dell'Olio and Tony Donk use detailed case studies to discuss 10 models of teaching and demonstrate how they can be connected to state content standards and benchmarks, as well as technology standards. This book provides readers with the theoretical and practical understandings of how to use models of teaching to both meet and exceed the growing expectations for research based instructional practices and student.